Generational and ideological gaps in democratic support: Seeds of deconsolidation in post-crisis Southern Europe? - Tsatsanis, E.; Enrico Borghetto; Freire, A.; Montero, J. R. (A generational divide?: Age-related aspects of political transformation in post-crisis Southern Europe, 2023)
Tsatsanis, Emmanouil, Enrico Borghetto, André Freire, José Ramon Montero (2023), «Ideological and generational gaps in forms of support for democracy in Southern Europe in the aftermath of the economic crisis», Emmanouil Tsatsanis, Marco Lisi & André Freire (editors) (2023), A Generational Divide? Age-related Aspects of Political Transformation in Post-crisis Southern Europe, London, Routledge, pp. 74-102. https://www.routledge.com/A-Generational-Divide-Age-related-Aspects-of-Political-Transformation/Tsatsanis-Lisi-Freire/p/book/9781032346380#